A New Method of Diminishing Errors of Form Generated by the Imprecision of CNC Machines. (2016) - Wagner, Erika
Abstract: During the processing of the helical surfaces on CNC machines, independent of the number of axes of the machine, there will certainly appear geometric deviations from the theoretical profile. Errors of form, which appear in this situation, can be detected through successive measurements. In order to diminish them, it is possible to use a method of compensation the deviations previously measured, which consists in adapting the CNC code used to obtain the helical profiles to the conditions required by the imprecision generated by the geometry of the machine.